EVALUASI PENGGUNAAN OBAT PADA PENDERITA DIARE AKUT PASIEN PEDIATRI DI INSTALASI RAWAT INAP RUMAH SAKIT ADVENT BANDAR LAMPUNG PERIODE JULI – DESEMBER 2019 - Subur Widodo; Novita Tri Wahyuni; Lea Yekti Utami (Fakultas MIPA Universitas Tulang Bawang Lampung, 2020)
Abstract Acute diarrhea is diarrhea that lasts less than 14 days. Regarding its severity, acute diarrhea is classified as mild, moderate or severe. Mild when signs of dehydration are not observed, moderate when there are mild or moderate signs of dehydration and rehydration can be done orally and severely when it results in more intense dehydration with or without electrolyte disturbances, and requires intravenous therapy. Diarrhea disease in the Inpatient Installation Bandar Lampung Adventist Hospital is the 10 biggest diseases and has never been evaluated on the use of drugs in pediatric patients. This study aims to evaluate the use of drugs in patients with acute diarrhea inpatients installation at the Bandar Lampung Adventist Hospital calculated from July to December 2019 data. This research is a descriptive study with retrospective data collection. The data collection process begins by tracing medical records of acute diarrhea patients. The population of acute diarrhea cases was 152 patients and then the number of samples obtained was then selected according to the inclusion criteria as a sample of 60 patients. From the research results it is known that the use of drugs in patients with acute diarrhea in pediatric patients includes antibiotics, electrolyte solutions, analgesic/antipyretics, antidiarrheals and other drugs (antihistamines, supplements and probiotics). The validation of drug use on the right indicators, the right patient and the right dose has reached 100%, the right indicator is 37% and the drug is 63% incorrect, this is due to the use of antibiotics without laboratory results that show acute diarrhea due to infection. Keywords: acute diarrhea, evaluation of drug use, pediatric